"I Said Something Wrong": Transworld Obligation in Yesterday. Issue 2 (June 2021) - Gimbel, Steven; Wilk, Thomas
Abstract : Danny Boyle's film Yesterday (2019) is a contemporary morality play in which the main character, Jack Malik, a failing singer-songwriter, is magically sent to a different possible world in which the Beatles never existed. Possessing his memory of the Beatles' catalogue in the new possible world, he is now in sole possession of an extremely valuable artifact. Recording and performing the songs of the Beatles and passing them off as his own, he becomes rich, famous, and deeply unhappy. Once he confesses his wrong-doing, however, he is redeemed and his life becomes wonderful. The presupposition that underlays the plot is that in claiming authorship of the songs of the Beatles in a world in which the Beatles never existed, he is acting immorally. But on what theoretical grounds can this intuitive judgment be justified? Can one plagiarize work for which there is no author in one's world? Saul Kripke, in Naming and Necessity, dubs terms that refer in all possible worlds to be "rigid designators" and considers the metaphysics necessary to support them. In this case, it is not reference but moral responsibility that is invariant under changes of possible world and so we must ask a similar question for "rigid obligators." We argue that a virtue ethics approach is the only way to support the foundational moral intuition.